2021
DOI: 10.1038/s41585-021-00477-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of disease severity in urinary tract infection

Abstract: The most common and lethal bacterial pathogens have co-evolved with the host. Pathogens are the aggressors, and the host immune system is responsible for the defence. However, immune responses can also become destructive, and excessive innate immune activation is a major cause of infection-associated morbidity, exemplified by symptomatic urinary tract infections (UTIs), which are caused, in part, by excessive innate immune activation. Severe kidney infections (acute pyelonephritis) are a major cause of morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 268 publications
(363 reference statements)
1
34
0
Order By: Relevance
“…Mechanisms of APN pathogenesis and innate immune activation have been extensively studied and reviewed 4 6 , 29 . Briefly, pathogen-specific recognition mechanisms activate a rapid innate immune response in infected tissues, leading to inflammation and the mobilization of an antibacterial defence 65 .…”
Section: Disease Determinants In Acute Pyelonephritismentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanisms of APN pathogenesis and innate immune activation have been extensively studied and reviewed 4 6 , 29 . Briefly, pathogen-specific recognition mechanisms activate a rapid innate immune response in infected tissues, leading to inflammation and the mobilization of an antibacterial defence 65 .…”
Section: Disease Determinants In Acute Pyelonephritismentioning
confidence: 99%
“…Mechanisms of innate immune activation and essential effector functions in APN have been mapped using cellular infection technology, animal models and clinical studies 4 , 10 , 11 , 14 , 16 , 18 , 19 , 32 , 75 80 . Key regulators of UTI severity have been evaluated using gene knockout technology and their relevance to human disease has been verified in clinical studies 10 , 11 , 29 , 78 .…”
Section: Disease Determinants In Acute Pyelonephritismentioning
confidence: 99%
See 1 more Smart Citation
“…UTI is a wide spectrum of diseases including bladder infection (cystitis), kidney infection (pyelonephritis), and systemic infection with multiorgan failure (in severe case) ( Ambite et al., 2021 ). UTI usually starts in the bladder and can spread to the kidney ( Nielubowicz and Mobley, 2010 ; Klein and Hultgren, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Uroepithelial cells are usually the first to respond to microbial challenge and then orchestrate the subsequent host response by release of cytokines, other mediators of inflammation, and complement proteins and stimulate the influx of neutrophils ( Spencer et al., 2014 ; Jones-Freeman et al., 2021 ). However, most human UPEC strains are resistant to complement-mediated killing ( Li et al., 2009 ; Bjanes and Nizet, 2021 ), and several lines of study have suggested that these bacteria mediate excessive inflammatory responses that cause uroepithelial destruction ( Wullt et al., 2003 ; Ambite et al., 2021 ; Paludan et al., 2021 ), impair innate immune cell function, and lead to chronic and recurrent UTI ( Hannan et al., 2010 ; Choudhry et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%